The Impact of Medical Waste on The Health and Safety of Workers in Government Hospitals in Light of The Events of The Return Marches- 2018 (Dar Al-Shifa Hospital - Case Study) - Albatniji, Omar ibraheem; Mohammed, Khaldun Khalid; Schokry, Abed Ahmad; El-Ashgar, Nizam Mahmoud; Al- Agha, Mohammad R. (Journal of Risk and Crisis Management, 2019)
This study aimed to identify the effectiveness of the application of the medical waste management system in Al-Shifa Hospital in Gaza, and contribute to building the concept of integrated management of medical waste treatment. The researchers used the descriptive analytical approach to achieve the results and answer the questions of the study through interviews with the staff who are directly related to the management of medical waste. It was clear from the results of the study that insufficient medical preventive measures were taken with regard to the preventive vaccination of working crews, especially cleaners. The large workload, the apparent lack of medicines & medical supplies and the beds of the affected people also affected the performance of the staff and the quality of service provided to the sick and injured. The results of the study also showed that the events of the Return Marches had a great impact on the performance of the work crews through the large increase in the volume and pressure of work, which in turn led to an increase in the volume of medical waste, especially human organs. One of the most important recommendations of this study is the necessity of enacting the relevant laws to control the medical waste management system and activating this system through coordinating efforts, defining responsibilities among the various concerned bodies, activating the role of the inspection and control unit at the Ministry of Health to conduct visits and periodic evaluation of medical waste management, conducting tests and vaccinations periodically and according to a specific program for the hospital staff. In addition to the allocation of closed places to collect medical waste containers after sorting instead of leaving it in the facilities and corridors of the hospital waiting to be transferred to the storage site.
Keywords: Medical Waste; Hazardous Materials; Gaza Strip; Medical Hospital Waste